Estrategias de solución de problemas aplicadas por ajedrecistas de diferente nivel (2017)
We studied the different problem solving strategies applied by chess players of different levels, with the goal of creating more intregrative programmes that are better at perfecting the training of chess players of all ages. Hence, this research might guide the selection of young talented players in sports schools in our country, and from the psychological point of view, the most relevant issue is how chess players solve problems in daily life using what they have learned through chess. The main goal was to identify problem solving strategies in chess players of different levels, and the specific goals were to determine the strategies used by chess players in logical thinking tasks, to define the strategies used by the sample in the solution of chess games, and to determine whether more experienced players use better strategies. The variables were: problem solving, logical thinking, thinking, strategy, and efficacy, measured with the Chess Test proposed by Przewoznik y Soszynski (2004) and the logical thinking test by Tobin & Capie (1981). The sample consisted of eight participants, and data were processed with Excel. We found that the five domains proposed in the logical thinking test (proportionality, variable control, probability, correlation, and combinatorial operations) are also present in the Chess Test, and that more experienced players had higher efficacy at solving chess positions. The Tobin and Capie test showed large similarities in terms of strategies.